Safety, efficacy, and clinical outcomes of transcatheter tricuspid valve replacement: One-year follow-up - Mao, Yu; Li, Lanlan; Liu, Yang; Zhai, Mengen; Ma, Yanyan; Xu, Chennian; Jin, Ping; Yang, Jian (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective Tricuspid regurgitation (TR) is a common type of valvular heart disease and is closely associated with adverse clinical outcomes. This study describes the experience of a single center with severe TR who were treated with transcatheter tricuspid valve replacement (TTVR). Methods This project was a single-center, observational study. From September 2020 to May 2021, 15 patients in the Xijing Hospital with severe or extremely severe TR at high risk of traditional surgery were enrolled. All patients had computed tomography, transthoracic echocardiography, and transesophageal echocardiography (TEE) examinations to assess the tricuspid valve and the anatomy of the right heart. The LuX-Valve was implanted under the intraoperative guidance of TEE and X-ray fluoroscopy. Data were collected at baseline, before discharge, and at 30 days, 6 months, and 1 year postoperatively. Results The LuX-Valves were successfully implanted in all 15 patients. TR was significantly reduced to ≤2+. After the valves were implanted, intraoperative TEE showed no/trace regurgitation in 13 patients, mild regurgitation in 1 patient, and moderate regurgitation in 1 patient. The median duration of the procedure was 140.0 (110.0, 180.0) minutes, and the median time in the intensive care unit was 2.0 (1.0, 12.0) days. One patient died on postoperative day 12 of a pulmonary infection that was considered unrelated to the procedures or the devices. During the 1-year follow-up, no patients died, and 1 patient (7.1%) experienced device thrombosis. Transthoracic echocardiography showed that 12 patients had no/trace regurgitation, and 2 patients had mild regurgitation. The remaining 14 patients (100.0%) reached the primary end point. The number of patients who survived at 1 year with New York Heart Association (NYHA) functional class II was higher than that before the surgery (11/14 vs. 0/15, P=9.11×10-4), and no device-related complications occurred. Patients with peripheral edema and ascites decreased from 100.0% and 46.7% at baseline to 28.6% and 14.3% at 1 year (P=1.57×10-3 and 2.53×10-2). Conclusions TTVR is associated with RV remodeling, increased cardiac output, and improvement in NYHA functional class. Using the LuX-Valve for TTVR to treat patients with severe TR is a feasible and relatively safe method with reliable clinical results.